2000
DOI: 10.1046/j.1365-2036.2000.00795.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of Helicobacter pylori infection with dual resistance to metronidazole and clarithromycin in Hong Kong

Abstract: The prevalence of metronidazole-resistant H. pylori strains remained static whilst the prevalence of clarithromycin-resistant strains was not rare in Hong Kong. An alarming 7.2% of patients were resistant to both the antimicrobials, which had a definite impact on treatment success. All cases of resistance to clarithromycin were due to A2144G mutation in 23S rRNA of H. pylori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
98
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 31 publications
11
98
0
Order By: Relevance
“…Therefore we need to find means to attenuate gastric inflammation and provide cytoprotection against H. pyloriinduced cytotoxicity. 23 Our study showed H. pylori-associated chronic active gastritis and gastric carcinogenesis to be effectively suppressed by oral administration of canolol at 0.1% in the diet. In addition, iNOS, COX-2, and inflammatory cytokine IL-1b, IL-12 and TNF-a mRNA expression levels were substantially decreased after canolol administration in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore we need to find means to attenuate gastric inflammation and provide cytoprotection against H. pyloriinduced cytotoxicity. 23 Our study showed H. pylori-associated chronic active gastritis and gastric carcinogenesis to be effectively suppressed by oral administration of canolol at 0.1% in the diet. In addition, iNOS, COX-2, and inflammatory cytokine IL-1b, IL-12 and TNF-a mRNA expression levels were substantially decreased after canolol administration in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 89%
“…20 Amoxicillin resistance is uncommon. According to the latest research from Taiwan 21 and Hong Kong, 22 primary resistance to metronidazole, clarithromycin and amoxicillin was found in 32%, 6% and 0%, and 56%, 2% and 0.4%, respectively. Furazolidone is an old and cheap but effective antimicrobial with bactericidal or bacteriostatic activity against many Grampositive and Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of resistance to these anti-microbial agents varies with gender, ethnic group and country of origin (Table 1) [41] . It was recently reported from Hong Kong that almost 50% of pre-treatment strains of H. pylori were resistant to metronidazole and over 10% to clarithromycin [42] . The efficacy of treatment for H. pylori is significantly decreased in the presence of pre-treatment anti-microbial resistance and the likelihood of this should influence the chosen regimen (Table 1, Figure 1) [5,41] .…”
Section: H Pylori Eradication Treatmentmentioning
confidence: 99%
“…Eradication is defined as negative tests for the bacterium four weeks, or longer, after the end of antimicrobial therapy [42] . Failure to detect H. pylori on tests done less than four weeks after the end of therapy may give false negative results because clearance, or uppression of H. pylori may occur during treatment, followed by rapid recrudescence of the original infection.…”
Section: H Pylori Eradication Treatmentmentioning
confidence: 99%
See 1 more Smart Citation